2004
DOI: 10.1158/0008-5472.can-04-0552
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of Estrogen Receptor β in Ovarian Carcinogenesis

Abstract: Knockout and expression studies suggest that estrogen receptor ␤ (ER␤) plays a prominent role in ovarian function and pathology. Moreover, ovarian cancers are characterized by high morbidity and low responsiveness to anti-estrogens. Here we demonstrate, using quantitative PCR to measure ER␣ and ER␤ levels in 58 ovarian cancer patients, that ER␤ expression decreased in cysts and ovarian carcinomas as compared with normal ovaries and that this decrease is attributable only to a selective loss in ER␤ expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 52 publications
7
56
0
1
Order By: Relevance
“…These initial findings had not taken into account the presence of ER subtypes. Both ERa and ERb were found to be present in both normal ovarian tissues and ovarian cancer tissues, with a possible reduction of ERb expression as tumors progress (Bardin et al 2004a, Chan et al 2008. The loss of ERb expression indicates that ERb exerts tumor-suppressive functions and may have a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…These initial findings had not taken into account the presence of ER subtypes. Both ERa and ERb were found to be present in both normal ovarian tissues and ovarian cancer tissues, with a possible reduction of ERb expression as tumors progress (Bardin et al 2004a, Chan et al 2008. The loss of ERb expression indicates that ERb exerts tumor-suppressive functions and may have a protective role.…”
Section: Discussionmentioning
confidence: 99%
“…A similar downregulation of ERβ has also been noted in prostate, breast, and colon tumors (CAMPBELL-THOMPSON;LYNCH;BHARDWAJ, 2001;ROGER et al, 2001;CHENG et al, 2004). It has been reported that ERβ up-regulates apoptosis in ovarian cancer cells (BARDIN et al, 2004b) and enhances FasL expression, a major extrinsic apoptotic regulator, in normal ovarian cells (SAPI et al, 2002 CHENG et al, 2004) cancer cells. Thus, similar to the cow, luteolysis in the dog is multifactorial and can occur via both apoptotic pathways .…”
Section: Casp3 Casp8 Casp9 Bax Fas Mki67 Cyp19a1 Cyp11a1 Hsb3supporting
confidence: 55%
“…Accordingly, the ratio of ERa to ERb was observed to increase during carcinogenesis [Pujol et al, 1998;Rutherford et al, 2000], strengthening the concept of ERa as promoting tumorigenesis while ERb of preventing it. As additional proof is loss of the ERb expression could be one of the leading events to breast and ovarian carcinogenesis [Lazennec et al, 2001;Bardin et al, 2004]. Mechanistic studies of the functions of ERb are revealing the reason behind its anti-proliferative effects in contrast to ERa.…”
Section: Estrogen Receptor B Another Significant Player In Estrogen mentioning
confidence: 99%